Collaboration and information sharing in dyadic supply chains: A literature review over the period 2000–2012 (Estudios Gerenciales, 2014)
Information sharing and coordination between the agents of a supply chain are considered to be an effective strategy for improving its global performance. This paper presents an updated review of current literature examining the impacts of information sharing and collaboration strategies on supply chain dynamic performance, with particular focus on dyadic structure. To achieve this, a systematic review approach is followed over the period 2000–2012, intending to ensure that the process is reproducible and auditable. A comprehensive taxonomy is also presented, highlighting strategic and operational impacts of collaborative structures. The analysis revealed that collaborative and information sharing issues underlined 10 years ago still require further attention from researchers.